Historical Experience in Spiritual and Moral Education of Warriors Through Military Rituals in Central Asia - Kodirov Otabek Maxammadjonovich, Gaipov Ravshan Abdujalilovich, Shakirov Shukhratjon Taxirovich, Akramova Shakhnoza Abrarovna (International Journal of Modern Agriculture, 2021)
From a historical point of view, the article examines the role of military rituals in the spiritual and moral education of soldiers, in the formation of their moral and combat qualities, theoretical aspects of military rituals, their origin and development in Central Asia, analyzes the influence on them of various external and internal factors, including customs, traditions of different peoples and religions. Various forms and methods of conducting military rituals in the daily and service-combat activities of units in the armies of various states and empires located on the territory of modern Central Asia are considered, their subsequent systematization, taking into account the characteristics of a certain period of time, as well as the educational role in improving the moral and moral atmosphere and strengthening military discipline in military collectives and, in general, in increasing their combat readiness and combat ability at the present stage of development of the national army of Uzbekistan.